Laser lock-in thermography on dental inspection using infrared laser - Wong, Jin Wei (Nanyang Technological University, 2019)
Common dental X-rays diagnosis is precise in dentistry, but it has caused a lot of concerns due to its ionizing radiation nature and uncomfortable patient experiences. Detection of the defects in the teeth and evaluation of dental restoration in a non-invasive way is of paramount importance in clinical practice. With the use of laser lock-in thermography, it has proven effective with good sensitivity and resolution. By preventing damage to the dental pulp, low laser power must be used. The defect will be propagated with subsurface thermal waves. The phase and amplitude image will be processed with better resolution. In this project, the author will investigate the use of laser lock-in thermography for crack detection on dental tooth.